THE CONTEMPORARY ENVIRONMENT ON THE APPLICATION SHARIAH SUPPLEMENTARY CONTRACTS IN ISLAMIC BANKING PRODUCTS OF THE ISLAMIC BANKS - Jais, Muhammad; Mahdi, Sayed (Universitas Syiah Kuala, 2024)
In the contemporary environment on the application of Shariah supplementary contracts in Islamic banking instruments, generally used as supporting contracts, the supporting contracts are often important because they act to complete many aspects of services, products, and banking. However, many supporting contracts are created to cater mostly to the specific situation, and most of them require proper Aqad as well. Therefore, such contracts are also considered a facility to provide specific outcomes for the customer. Supporting contracts can be implemented in Islamic banking and finance (IBF) because they make it easier to conduct banking activities and also provide mutual benefits between customers and IBF. This study uses the qualitative approach by adopt library-based research and document analysis. This study employs a qualitative approach by the useof document analysis and library-based research. The National Sharia Board-MUI (DSN-MUI) published books, journals, and fatwas. Policy documents and other data date also gathered for this study.This study found that the Shariah supporting contract for Kafalah Bank Guarantees can provide benefits for customers to obtain goods and services with a delay in paying the price. The hybrid supporting contracts of Kafalah and Wakalah bi al-Istithmar can benefit Islamic banks.Keyword: Shariah supplementary contract, Islamic Bank, Kafalah, Wakalah